Activation of microglia bolsters synapse formation - Cristovão, Gonçalo (2014)
This work was supported by PEst- C/SAU/LA0001/2013-2014,by FEDER, through Programa Operacional Fatores de Competitividade—COMPETE and by national funds,through FCT—Fundação para a Ciência e aTecnologia through grants PTDC/SAU-NEU/104100/2008, EXPL/NEU-NMC/0541/2012 and by Marie Curie Actions, International Reintegration Grant, 7th Framework Programme EU, to Ramiro D. Almeida. FCT supports Maria J. Pinto (SFRH/BD/51196/2010) and Catarina Gomes (SFRH/BPD/63013/2009).